2021
DOI: 10.1590/1980-4415v35n69a10
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peer Instruction on Ninth Grade Students’ Trigonometry Knowledge

Abstract: In this study, we conducted peer instruction (PI) activities to promote student participation in the learning process and test the hypothesis that PI improves student achievement. Two ninth-grade classes were randomly assigned as treatment and control groups. Pre-test and post-test data were obtained for measuring mathematics achievement in trigonometry. Data were analyzed using analysis of covariance procedures with an alpha significance level of 0.05. Results indicated no significant effects of peer instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…9 out of 10 studies found that PI showed positive impacts on the students' achievement in various disciplines. Only 1 study found that PI did not significantly impact students' achievement (Nuri et al, 2021). The ineffectiveness of PI on students' achievement may be attributed to students simply selecting the most frequent response or just changing their ideas depending on the agreement of nearby students, rather than learning through PI (Perez et al, 2010).…”
Section: Impacts Of Peer Instruction (Pi) At the Tertiary Levelmentioning
confidence: 93%
See 3 more Smart Citations
“…9 out of 10 studies found that PI showed positive impacts on the students' achievement in various disciplines. Only 1 study found that PI did not significantly impact students' achievement (Nuri et al, 2021). The ineffectiveness of PI on students' achievement may be attributed to students simply selecting the most frequent response or just changing their ideas depending on the agreement of nearby students, rather than learning through PI (Perez et al, 2010).…”
Section: Impacts Of Peer Instruction (Pi) At the Tertiary Levelmentioning
confidence: 93%
“…Based on the meta-analysis, it was found that PI has been used in teaching mathematics (Awinoouko, 2018;Nuri et al, 2021;, physics (Antwi et al, 2016;Atasoy et al, 2014), ICT (Wang & Murota, 2016) and history (Kaviza, 2021). Only 8 out of the 26 studies had discussed the implementation of PI at the secondary school level.…”
Section: Impacts Of Peer Instruction (Pi) At the Secondary Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…In ninth grade, they learn new and relatively difficult topics such as trigonometry, binomial expansion, arithmetic, geometric series, etc. (Balta et al, 2021).…”
Section: Rq5: Is There An Association Between Students' Math Emotions...mentioning
confidence: 99%